Four‐dimensional phase‐contrast vastly undersampled isotropic projection reconstruction (4D PC‐VIPR) MR evaluation of the renal arteries in transplant recipients: Preliminary results. Issue 2 (2nd February 2017) - Motoyama, Daisuke; Ishii, Yasuo; Takehara, Yasuo; Sugiyama, Masataka; Yang, Wang; Nasu, Hatsuko; Ushio, Takasuke; Hirose, Yuko; Ohishi, Naoki; Wakayama, Tetsuya; Kabasawa, Hiroyuki; Johnson, Kevin; et al.
Abstract : Purpose: To assess the performance of four‐dimensional phase‐contrast vastly undersampled isotropic projection reconstruction (4D PC‐VIPR) at 3.0T in depicting intrarenal arteries compared with computed tomography angiography (CTA), and its correlation with arterial flowmetry in comparison with Doppler ultrasonography (DUS). Materials and Methods: In our prospective single‐arm study, subjects were 25 patients who underwent renal transplant‐related surgery at our hospital between July 2011 and June 2015. In the morphological study, depictions of renal artery branches delineated by magnetic resonance angiography (MRA)/4D PC‐VIPR without gadolinium contrast agent were compared in seven living transplant recipients with the same kidney delineated by CTA in seven living transplant donors. In the flowmetric study, flow velocities in the renal (main stem), segmental, and interlobar arteries during systole and diastole were measured in 12 recipients using noncontrast MRA/4D PC‐VIPR, and were compared with those obtained from DUS. Results: Concerning MRA, average confidence levels of delineation rated by six observers for secondary to third level renal artery branches were 82.9–100% and for the fourth to fifth branches were 60.8–89.7% (average kappa value of 0.588 [95% confidence interval: 0.522–0.653]). Total flow velocities measured using 4D PC‐VIPR and DUS demonstrated significant correlations during both systole and diastole with acceptable bias ( r = 0.902; P < 0.001 in systole and r = 0.734; P < 0.001 in diastole). Conclusion: 4D PC‐VIPR was useful in generating both morphological and hemodynamic information for evaluation of transplant intrarenal arteries without the need for contrast media. Level of Evidence: 2 Technical Efficacy : Stage 2 J. MAGN. RESON. IMAGING 2017;46:595–603